Oculogyric crisis mimicked epilepsy in a Chinese aromatic L-amino acid decarboxylase-deficiency patient: A case report - Wang, Hongmei; Li, Jiahong; Zhou, Ji; Dai, Lifang; Ding, Changhong; Li, Mo; Feng, Weixing; Fang, Fang; Ren, Xiaotun; Wang, Xiaohui (Frontiers in Neurology, 2022)
Background: Aromatic amino acid decarboxylase (AADC) deficiency is a rare, autosomal recessive neurometabolic disorder with heterogeneous phenotype, including hypotonia, movement disorders, autonomic dysfunction, and developmental delay. Here, we reported a Chinese patient with AADCD who was initially misdiagnosed with epilepsy. Case Presentation: The proband was a 4-month old Chinese girl, representing hypotonia, episodes of oculogyric crises with dystonia, and delayed developmental milestones. The patient was first misdiagnosed with epilepsy because of the similarity between episodes of oculogyric crisis and epileptic seizure. The accurate diagnosis of AADCD was established through analysis of neurotransmitters in cerebrospinal fluid (CSF). The genetic test confirmed the patient carried novel compound heterozygous mutations in the DDC gene: c.419G>A (p.G140E) and c.1375C>T (p.H459Y). Conclusion: This study reported a patient with AADCD initially misdiagnosed as epilepsy. Two novel missense mutations in the DDC gene were identified from the patient and her family. Little infants with epileptic-like attacks should consider AADCD. Accurate diagnosis of AADCD is essential for drug choice and patient management.